STUDY OF BEHAVIOR AND ABOUT FOOD POSTPARTUM MOTHER OF THE BANJAR TRIBE IN PALUH KURAU VILLAGE - Nova Linda Rambe; Ida Yustina; Nurmaini Nurmaini; Kintoko Rochadi; Fikarwin Zuska (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Indonesian people cannot be separated from behavior and habits based on culture or customs that are believed to provide positive benefits and impacts. The Banjar tribe is an indigenous people who inhabit most of South Kalimantan. This tribe has spread, one of which is in Paluh Kurau Village, Hamparan Perak District. Nifas mothers in the Banjar tribe also know the taboos passed down from their ancestors. The strong taboo associated with the postpartum period causes the Banjar tribe to always be associated with local traditions. This research was a qualitative research with an ethnographic approach. The research was conducted in Paluh Kurau Village, Hamparan Perak District. Respondents in this study were postpartum mothers who carried out the Banjar tribal tradition which was taken by purposive sampling. Data collection techniques were carried out by interviews and FGD (Focus Group Discussion). Total informants in this study were 11 people. The results of the study revealed that the behavior of postpartum mothers of the Banjar tribe in Paluh Kurau Village was grouped into 3 categories of receiving treatment, namely from village shamans, customs and from health workers. While the taboos of postpartum mothers are grouped into 3 categories, namely behavioral and dietary restrictions.